2017
DOI: 10.5539/ijms.v9n4p76
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Materialism in the Effect of Perceived Value on Purchase Intention of Counterfeits of Luxury Brands

Abstract: The use of counterfeits of luxury brands has become a phenomenon in Turkey in recent years since they are the most significant facilitator for consumers to reach luxury consuming products. Limited number of studies in the literature shows that consumers prefer counterfeits of luxury brands for a variety of reasons. Within this study, it is believed that perceived value of products in consumers' minds and consumers' materialistic tendencies demonstrating the worth attached to physical assets could have an impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Consumers learn materialistic values from family, friends, and social media. Many studies have documented that young adolescents who spend more time on social media develop materialistic values, leads to high purchase intentions (Kalyoncuoglu & Sahin, 2017).…”
Section: Materialism and Purchase Intentionsmentioning
confidence: 99%
“…Consumers learn materialistic values from family, friends, and social media. Many studies have documented that young adolescents who spend more time on social media develop materialistic values, leads to high purchase intentions (Kalyoncuoglu & Sahin, 2017).…”
Section: Materialism and Purchase Intentionsmentioning
confidence: 99%
“…Perceived materialistic value has its roots in materialism defined as a "set of centrally held beliefs about the importance of possessions in one's life" (Richins & Dawson, 1992, p. 308). In recent studies, Hudders and Pandelaere (2012) and Kalyoncuoglu and Sahin (2017) found that materialism was positively associated with luxury consumption as materialists acquire possessions to conspicuously display them, and they equate luxury consumption with personal happiness. Based on the literature reviewed, the following hypothesis is proposed: H3: The consumer's perceived individual value of luxury brand/service is an appropriate criterion for value-based segmentation of the U.S. luxury consumer.…”
Section: Individual Valuementioning
confidence: 99%
“…Moreover, these figures are only based on 2016 customs seizure data, and do not include counterfeit products produced and consumed in various countries, or pirated products distributed through the Internet. At present, counterfeit goods have appeared in many industries, ranging from luxury handbags, perfume, and machine components to chemical products [4][5][6]. More seriously, some counterfeit goods even threaten the safety of human life, such as counterfeit auto parts, medical equipment with incorrect parameters, counterfeit tablets, counterfeit baby milk powder, etc.…”
Section: Introductionmentioning
confidence: 99%